311 Can a Brief Sleep Education Training Improve Sleep Quality Among Shipboard Sailors?. (3rd May 2021) - Harrison, Elizabeth; Schmied, Emily; Perez, Vanessa; Hurtado, Suzanne; Glickman, Gena
Abstract: Introduction: Sleep disturbance is pervasive among active duty military service members (ADSM) and has serious adverse effects on performance and health. Interventions designed to improve sleep in operational settings are critical to maintain the health and readiness of this at-risk population. The objective of this study is to evaluate a novel sleep education program developed for ADSM. Methods: Participants were U.S. Sailors (N=150; 82.7% male, 35.3% <25 years old) assigned to either an intervention (44.7%) or control (55.3%) condition. Intervention participants attended the Circadian, Light, and Sleep Skills program for military personnel ("CLASS-M"). The 30-minute education program was designed to teach ADSM how to maximize sleep quality in operational environments. All participants completed a questionnaire at both baseline and 2 months post-intervention assessing demographics, sleep quality (Pittsburgh Sleep Quality Index; PSQI), sleep-related behaviors, knowledge and motivation. During the follow-up period, participants went underway for 2–8 weeks. Results: At baseline, scores were comparable for the PSQI (Control: 8.58±0.35 vs. Intervention: 8.58±0.38), sleep behaviors (12.26±0.35 vs. 11.32±0.38; Range: 0–17), sleep-related knowledge (0.48±0.21 vs. 0.50±0.24; Range: 0–1), and sleep motivation (4.12±0.35 vs. 4.07±0.34; Range: 0–5). A significant group x time interaction indicating benefits for the intervention group were observed on PSQI (F (1, 139) = 7.99, p=0.005), knowledge (F (1, 139) = 36.54, p<0.001), and behaviors (F (1, 139) = 4.75, p=0.03), but not motivation (p>.05). Main effects of group were observed (p<0.05) on PSQI and sleep knowledge only. Conclusion: Study results indicate that participation in a brief, educational program prior to deploying may improve ADSM's sleep quality. Future research is needed to explore mechanisms of intervention effect, and to determine best practices for disseminating such programs force-wide. Support (if any): This work was supported by Defense Health Program 6.7 under work unit no. N1634. The views expressed in this article are those of the authors and do not necessarily reflect the official policy or position of the Department of the Navy, Department of Defense, nor the U.S. Government.